A study on flow as affected by the shape and wind speed of ventilated seat - Kwang Choi, Kye; Ung Cho, Jae (International Journal of Engineering and Technology, 2018)
Background/Objectives: We studied the ventilated seats with amenities. The study has its purpose in checking the flow as affected by the shape of the ventilated seats and thereby acquiring the design factors.Methods/Statistical analysis: In order to acquire the design factors for ventilated seats as affected by the shapes and wind speeds of the different models, we used CATIA program to design the shape, of which the flow was analyzed with ANSYS CFX program. Thus, we have acquired the design factors for ventilated seats, which data can be used to ensure higher levels of efficiency as compared to the shapes before.Findings: For analyzing, we placed an inlet at the vent at the bottom and placed an outlet at the top by setting a boundary around it. From the setup, which had the initial wind speed at 15m/s, the wind speed within the boundary was 29.91m/s for model 1 and 44.81m/s for model 2. At the initial wind speed of 30m/s, we got a wind speed of 60.25m/s for model 1 and 88.60m/s for model 2. As for the pressure and speed in the flow path as the initial wind speed of 15m/s, we got the maximum pressure of 100.60kPa and the maximum speed of 29.45m/s. For model 2, we got the maximum pressure of 102.30kPa and the maximum speed of 44.81m/s. At the initial wind speed of 30m/s, we got the maximum pressure of 102.30kPa and the maximum speed of 60.25m/s for model 1. For model 2, we got the maximum pressure of 105.10kPa and the maximum speed of 88.60m/s.Improvements/Applications: Through the data obtained from this analysis, the varied seat structure for additional amenities can be improved and applied with more design factors.Â Â